2021
DOI: 10.1002/pros.24269
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genomic features of SPOP‐mutant prostate cancer

Abstract: Background Inactivating missense mutations in the SPOP gene, encoding speckle‐type poxvirus and zinc‐finger protein, are one of the most common genetic alterations in prostate cancer. Methods We retrospectively identified 72 consecutive prostate cancer patients with somatic SPOP mutations, through next‐generation sequencing analysis, who were treated at the Johns Hopkins Hospital. We evaluated clinical and genomic characteristics of this SPOP‐mutant subset. Results SPOP alterations were clustered in the MATH d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 45 publications
3
16
0
1
Order By: Relevance
“…83,84 However, both studies could be seen as hypothesisgenerating given the small numbers 83 and mixed treatment populations. 84 Nakazawa et al recently reported on the outcome of 72 consecutive SPOPmut PCa from a single institution. 84 The SPOPmut PCa came from patients who had durable responses to first-line ADT, but their cohort included a heterogeneous group of patients with metastatic and nonmetastatic hormone-sensitive disease, as well as patients receiving concurrent chemotherapy and/or ASRi (i.e., abiraterone, enzalutamide).…”
Section: Ngs Reveals Distinct Subclasses Of Pca; Recurrent Spop Mutat...mentioning
confidence: 99%
See 2 more Smart Citations
“…83,84 However, both studies could be seen as hypothesisgenerating given the small numbers 83 and mixed treatment populations. 84 Nakazawa et al recently reported on the outcome of 72 consecutive SPOPmut PCa from a single institution. 84 The SPOPmut PCa came from patients who had durable responses to first-line ADT, but their cohort included a heterogeneous group of patients with metastatic and nonmetastatic hormone-sensitive disease, as well as patients receiving concurrent chemotherapy and/or ASRi (i.e., abiraterone, enzalutamide).…”
Section: Ngs Reveals Distinct Subclasses Of Pca; Recurrent Spop Mutat...mentioning
confidence: 99%
“…Two studies examining men with advanced PCa treated with ARSi both suggested SPOPmut PCa have an increased sensitivity to ARSi 83,84 . However, both studies could be seen as hypothesis‐generating given the small numbers 83 and mixed treatment populations 84 . Nakazawa et al recently reported on the outcome of 72 consecutive SPOPmut PCa from a single institution 84 .…”
Section: Ngs Reveals Distinct Subclasses Of Pca; Recurrent Spop Mutat...mentioning
confidence: 99%
See 1 more Smart Citation
“…The above evidence may explain why low CDK expression existed in the high GILncSig risk group in our results. Moreover, inactivating missense mutations in SPOP is one of the most common gene mutations in PCa, especially in the localized PCa ( 67 ). SPOP inactivation leads to overexpression of the androgen receptor (AR) and further promotes cell proliferation ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, PCa patients with mutant SPOP appear to delay the onset of ADT resistance to 42.0 (95% CI: 25.7–60.8) months. Also, the better outcomes in patients with mutant SPOP treated with abiraterone and enzalutamide were observed [ 42 , 43 ]. Therefore, it implies that SPOP mutation could enhance ADT effect by maintaining AR dependency.…”
Section: Hormone Therapymentioning
confidence: 99%